Proces badawczy jako proces decyzyjny – rozważania w kontekście teorii decyzji - Jarota, Martyna (Kultura-Społeczeństwo-Edukacja, 2023)
The research process is a component of many complex activities planned and then implemented by the researcher. At each of its stages, both in the conceptual phase and the implementation phase, the researcher identifies problem situations that require specific decisions to be made. Therefore, it is considered reasonable to analyze the research process in the light of the decision theory, which was done in this article. This theory provides a theoretical framework that allowed the research process to be identified as a multi-faceted decision-making process in which the researcher is the decision maker. Moreover, thanks to the decision theory, the conditions that accompany the research process, i.e. the conditions of uncertainty and risk, were described. Ways to minimize this risk are also presented. The article also focuses on research competences, thus assuming that they include competences related to effective decision-making. Therefore, the characteristics of an efficient researcher-decision maker were characterized. The considerations presented in this study may be the basis for making methodological criticism, as well as methodological reflection. Both criticism and methodological reflection can contribute to the development of research methodology, including the methodology of individual scientific disciplines.